Hydrochalcogenation of Symmetrical and Unsymmetrical Buta-1,3-diynes with Diaryl Dichalcogenides: Facile Entry to (Z)-1-(Organylchalcogeno)but-1-en-3-yne Derivatives - Venkateswarlu, Cheerladinne; Chandrasekaran, Srinivasan (Synthesis, 2015)
This work describes an efficient and stereoselective method for the hydrothiolation and -selenation of buta-1,3-diyne derivatives using diaryl disulfides or diselenides, respectively. In the presence of rongalite (HOCH2SO2Na) and potassium carbonate, buta-1,3-diynes undergo stereoselective addition of the thiolate or selenide anion generated in situ from diaryl disulfides or diselenides to afford the corresponding (Z)-1-sulfanyl- or (Z)-1-selanylalk-1-en-3-yne derivatives, respectively. The reaction of buta-1,3-diynes with diaryl disulfides or diselenides at higher temperature (70 °C) gave a mixture of monothiolation/selenation and bisthiolation/selenation products in moderate to good yields.
Keywords: hydrochalcogenation; buta-1,3-diynes; aryl dichalcogenides; rongalite; reductive cleavage